TiO2 / Co3O4 / AgBr ternary heterojunction composite material as well as preparation method and application thereof

By modifying the TiO2/Co3O4 binary composite material AgBr particles to form heterojunctions, it solves the problem of difficulty in efficiently removing antibiotics in water bodies in the prior art, achieves efficient adsorption and degradation, and improves photocatalytic activity and stability.

CN119633860APending Publication Date: 2025-03-18泰州学院
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411810375.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

现有技术难以高效去除水体中的抗生素,尤其是由于抗生素的大量使用导致环境污染问题严重,现有光催化技术在处理低浓度有机污染物时效率不高。

Method used

By citing AgBr particles, the surface modification of the TiO2/Co3O4 binary composite material is formed to form a heterojunction in point-to-face contact, improve its electron transfer efficiency, accelerate electron-hole separation, and improve the performance of catalyst oxidation and degradation.

Benefits of technology

It has achieved efficient adsorption and degradation of antibiotics in water bodies, improved photocatalytic activity, showed good stability and high adsorption rate, and had commercial promotion potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633860A_ABST
    Figure CN119633860A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalyst preparation, and particularly relates to a TiO2 / Co3O4 / AgBr ternary heterojunction composite material as well as a preparation method and application thereof. According to the invention, AgBr particles are introduced to carry out surface modification on a binary material to form a point-to-surface contact heterojunction, so that the electron transfer efficiency is improved, the electron-hole separation is accelerated, the oxidative degradation performance of the catalyst is improved, and the photocatalytic activity is further improved. When the TiO2 / Co3O4 / AgBr ternary heterojunction composite material provided by the invention is used for carrying out adsorption treatment on antibiotics in a water body, better stability and adsorption rate can be shown, and the TiO2 / Co3O4 / AgBr ternary heterojunction composite material has great commercial popularization potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a TiO2 / Co3O4 / AgBr ternary heterojunction composite material and a preparation method and application thereof. Background Art

[0002] With the acceleration of industrialization and the rapid growth of population, global environmental problems pose a great threat to human health. Most organic pollutants are difficult to degrade, inductive, bioaccumulative, migratory, and have negative effects on human health. Among them, the extensive use of antibiotics has further aggravated the problem of environmental pollution. Photocatalytic technology has become the most promising degradation technology by virtue of its advantages of using solar energy as energy, no secondary pollution to the environment and low cost. Semiconductor photocatalytic technology is the core component of photocatalysis, which removes toxic antibiotics in an efficient, low-energy and environmentally friendly way. It absorbs sunlight to drive semiconductor materials to generate electrons and holes to participate in oxidation-reduction reactions. It has the advantages of high efficiency, low cost, green and pollution-free. It is one of the widely used treatment technologies that can deeply treat low-concentration organic pollutants. Therefore, it is urgent to explore an efficient and environmentally friendly technology to remove antibiotics from water bodies. Summary of the invention

[0003] In view of this, in order to solve the deficiencies in the prior art, the present invention provides a TiO2 / Co3O4 / AgBr ternary heterojunction composite material. The present invention uses AgBr particles to modify the surface of the TiO2 / Co3O4 binary composite material to form a point-to-surface contact heterojunction, thereby improving its electron transfer efficiency, accelerating electron-hole separation, and improving the performance of catalyst oxidation degradation, thereby achieving efficient adsorption of antibiotics in water.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a TiO2 / Co3O4 / AgBr ternary heterojunction composite material, the preparation method comprising the following steps:

[0006] (1) Preparing a TiO2 / Co3O4 binary composite material; adding TiO2 to anhydrous methanol and ultrasonically mixing until uniform, adding 2-methylimidazole and stirring to obtain a mixed solution A; dropping a mixed solution of Co(NO3)36H2O and methanol into the mixed solution A, stirring at room temperature and then precipitating and aging, washing the product and drying it, and calcining it at high temperature to obtain a TiO2 / Co3O4 binary composite material;

[0007] (2) Preparing a TiO2 / Co3O4 / AgBr ternary heterojunction composite material: The TiO2 / Co3O4 binary composite material prepared in step (1) is homogenized by ultrasonication in deionized water, Ag2SO4 is added and stirred, and then a potassium bromide aqueous solution is added under dark reaction conditions and stirred in the dark; the product is washed and centrifuged, and dried to obtain a TiO2 / Co3O4 / AgBr ternary heterojunction composite material.

[0008] The molar ratio of Co(NO3)36H2O and TiO2 in the mixed solution A in step (1) is 3-27:3.

[0009] Preferably, the dosage ratio of TiO2, anhydrous methanol and 2-methylimidazole in the mixed solution A in step (1) is 0.072 mol:50 mL:0.032 mol; the dosage ratio of Co(NO3)36H2O, methanol and mixed solution A is 0.008 mol:50 mL:50 mL.

[0010] The stirring time in step (1) is 1h-5h, and the precipitation aging time is 3h-10h; preferably, the stirring time is 3h-5h, and the precipitation aging time is 5h-10h.

[0011] In the TiO2 / Co3O4 / AgBr ternary heterojunction composite material in step (2), the mass fraction of AgBr in the TiO2 / Co3O4 / AgBr ternary heterojunction composite material is 10-40%.

[0012] Preferably, the mass fraction of AgBr in the TiO2 / Co3O4 / AgBr ternary heterojunction composite material is 20-30%.

[0013] Further preferably, in step (2), the dosage ratio of the TiO2 / Co3O4 binary composite material, Ag2SO4, and potassium bromide aqueous solution is 0.0027 mol: 0.0013 mol: 50 mL; and the concentration of the potassium bromide aqueous solution is 0.016 mol / L.

[0014] The stirring time in step (2) is 2-8 hours, and the drying temperature is 50°C-80°C.

[0015] The present invention also provides a TiO2 / Co3O4 / AgBr ternary heterojunction composite material prepared according to the preparation method described above.

[0016] The present invention also provides an application of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material in the field of antibiotic adsorption in water.

[0017] The application is preferably to absorb tetracycline antibiotics in water.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention uses Co3O4 with abundant oxygen defects and oxygen vacancies prepared by high-temperature calcination of ZIF-67. After TiO2 is compounded with porous Co3O4, the band structure can be adjusted, the hole recombination of photogenerated electrons can be suppressed, and a larger specific surface area and abundant pore channels can be provided, thereby increasing the enrichment and absorption of organic pollutants on the surface of Co3O4. AgBr particles are further used to modify the surface of the TiO2 / Co3O4 binary composite material to form a point-to-surface contact heterojunction, thereby improving its electron transfer efficiency, accelerating electron-hole separation, and improving the performance of catalyst oxidation degradation, thereby improving the activity of photocatalysis. When the TiO2 / Co3O4 / AgBr ternary heterojunction composite material provided by the present invention is applied to the adsorption treatment of antibiotics in water bodies, it can show good stability and high adsorption rate, and has great potential for commercial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a SEM image of the prepared TiO2 / Co3O4 binary composite material; (b) is an enlarged image of (a);

[0021] Figure 2 is the XRD diagram of TiO2, Co3O4 and the TiO2 / Co3O4 binary composite material prepared in Example 1-Example 2;

[0022] Figure 3 is a SEM image of the prepared TiO2 / Co3O4 / AgBr ternary heterojunction composite material; (b) is an enlarged image of (a);

[0023] Figure 4 It is the element mapping diagram of the prepared TiO2 / Co3O4 / AgBr ternary heterojunction composite material;

[0024] Figure 5 The high-resolution electron microscopy (HRTEM) images of the prepared TiO2 / Co3O4 / AgBr ternary heterojunction composite material are shown in Figure 1. The resolution of (a) is 0.2 μm, and the resolution of (b) is 5 nm.

[0025] Figure 6 is the UV-Vis DRS graph of the prepared composite material; in the figure, (a) is the spectrum graph of absorbance changing with wavelength and (b) is the spectrum graph of photon energy changing;

[0026] Figure 7 is the photodegradation graph of tetracycline by the prepared composite material;

[0027] Figure 8 These are the EIS graphs of TiO2, Co3O4, 5-TCo, and 2-TCA; in the graph, (a) is the photocurrent curve and (b) is the electrochemical impedance graph;

[0028] Fig. 9 It is the PL graph of TiO2, Co3O4, 5-TCo, and 2-TCA;

[0029] Fig.10 It is the MS graph of TiO2, Co3O4, 5-TCo, and 2-TCA;

[0030] Fig.11 is an XPS graph of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material prepared in Example 3;

[0031] Fig.12 This is a diagram showing the degradation effect of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material prepared in Example 3 after 5 cycles. DETAILED DESCRIPTION

[0032] In order to more fully understand the technical contents of the present invention, the technical solutions of the present invention are further described and introduced below in conjunction with specific examples. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The preparation method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0033] It is clear to those skilled in the art that, hereinafter, unless otherwise specified, the materials and operating methods used in the present invention are well known in the art, the experimental methods used are conventional methods, and the materials and reagents used can be purchased from chemical reagent companies. The monomer Co3O4 described in the present invention can also be prepared by the following preparation method:

[0034] 2.3203 g of Co(NO3)36H2O was ultrasonically dissolved in 50 mL of methanol; 2.6198 g of 2-methylimidazole was ultrasonically dissolved in another 50 mL of methanol; during the stirring process, the Co(NO3)36H2O methanol solution was dropwise added to the 2-methylimidazole methanol solution, and the mixture was stably stirred for 3 h at room temperature. The solid product was precipitated and aged for 5 h to obtain the solid product; the solid product was washed with methanol 3 times, centrifuged, dried in a forced air drying oven at 60°C, and ground into powder in a centrifuge tube to prepare ZIF-67; ZIF-67 was placed in a 15 mL crucible, placed in a constant temperature box furnace and calcined at 550°C for 2 h to obtain the product Co3O4.

[0035] Example 1

[0036] Preparation of TiO2 / Co3O4 binary composite material: 5.7202g TiO2 was added to 50mL anhydrous methanol and ultrasonically treated until uniform, 2.6201g 2-methylimidazole was added and stirred to obtain a mixed solution A; 2.32g Co(NO3)36H2O and 15mL methanol mixed solution were dripped dropwise into the mixed solution A, stirred at room temperature for 3h, precipitated and aged for 5h, the obtained solid product was washed 3 times with anhydrous methanol, dried at 60℃ in a forced air drying oven, and then the product was placed in a constant temperature box furnace and calcined at 550℃ for 2h to obtain a TiO2 / Co3O4 binary composite material, recorded as 5-TCo, in which the mass ratio of TiO2 to Co3O4 was 9:1. Figure 1 is a SEM image of the prepared TiO2 / Co3O4 binary composite material; (b) is an enlarged image of (a); Figure 1 It can be seen that Co3O4 nanosheets cover the TiO2 surface.

[0037] Example 2

[0038] Referring to the preparation method in Example 1, TiO2 / Co3O4 binary composite materials with different mass ratios of TiO2 and Co3O4 were prepared by adjusting the amount of TiO2 added, and the products were respectively recorded as 1-TCo, 2-TCo, 3-TCo, and 4-Tco; the mass ratios of TiO2 and Co3O4 in each product were 1:9, 3:7, 5:5, and 7:3, respectively.

[0039] XRD is used to identify the structure of the prepared TiO2 / Co3O4 binary composite material. After the required test samples are prepared, the equipment and calibration of the instrument are carried out; data collection is performed on the required samples and then analyzed to obtain the data. Figure 2The XRD diagrams of TiO2, Co3O4 and the TiO2 / Co3O4 binary composite material prepared in Example 1-Example 2 are shown in FIG. 1 . In the figure, TiO2PDF#99-0008 corresponds to anatase TiO2, and TiO2PDF#99-0090 corresponds to rutile TiO2. Figure 2 It can be seen that the characteristic peaks of anatase TiO2 and Co3O4 can be seen in the XRD spectrum of the TiO2 / Co3O4 binary composite material. The XRD theory of the monomer Co3O4 is well consistent with the actual spectrum, and the purity is high. The content of Co3O4 in the composite TiO2 / Co3O4 binary composite material is low, resulting in a low peak intensity of Co3O4. However, it is still characterized, indicating that the construction of the TiO2 / Co3O4 binary composite material is successful.

[0040] Example 3

[0041] Take 0.5004g of the TiO2 / Co3O4 binary composite material prepared in Example 1 and add it to 100mL of deionized water for ultrasonic homogenization, then add 0.0418g of Ag2SO4 and stir evenly, add potassium bromide aqueous solution (0.0950gKBr, 50mL of deionized water) under dark reaction conditions and stir in the dark for 4h; the product is washed with deionized water 3 times, centrifuged, and placed in a forced air drying oven at 60°C to obtain a TiO2 / Co3O4 / AgBr ternary heterojunction composite material, which is recorded as 2-TCA. The mass fraction of AgBr in 2-TCA in the TiO2 / Co3O4 / AgBr ternary heterojunction composite material is 20%. Figure 3 is a SEM image of the prepared TiO2 / Co3O4 / AgBr ternary heterojunction composite material; (b) is an enlarged view of (a); Figure 3 It can be seen that the prepared ternary heterojunction composite material has a regular morphology, Co3O4 nanosheets cover the TiO2 surface, and the array remains basically unchanged during the Co3O4 deposition process; AgBr is evenly dispersed on the binary composite nanomaterial.

[0042] Figure 4 is the element mapping diagram of the prepared TiO2 / Co3O4 / AgBr ternary heterojunction composite material; Figure 4 It can be seen that the element mapping of relative elements Ti, O, Co, Ag and Br are evenly distributed on the Co3O4 structure, indicating that TiO2 and AgBr are well distributed on Co3O4.

[0043] Figure 5The following is a high-resolution electron microscopy (HRTEM) image of the prepared TiO2 / Co3O4 / AgBr ternary heterojunction composite material; in the figure, the resolution of (a) is 0.2μm, and the resolution of (b) is 5nm. Further measurements and characterizations of the detailed structure of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material showed that the d spacings were 0.248, 0.326, and 0.202nm, corresponding to the (101) and (110) planes of TiO2 and the (400) plane of Co3O4, respectively. The above results all confirm the successful preparation of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material.

[0044] Example 4

[0045] Referring to the preparation method of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material in Example 3, the addition amount of Ag2SO4 and potassium bromide aqueous solution was adjusted to prepare and synthesize TiO2 / Co3O4 / AgBr ternary heterojunction composite materials with different AgBr mass percentages. The products were respectively recorded as 1-TCA and 3-TCA; the mass fraction of AgBr in each product in the TiO2 / Co3O4 / AgBr ternary heterojunction composite material was 10% and 30% respectively.

[0046] Example 5

[0047] Figure 6 is the UV-Vis DRS diagram of the prepared composite material; in the figure, (a) is the spectrum diagram of absorbance variation with wavelength and (b) is the spectrum diagram of photon energy variation; Figure 6 It can be seen that the wavelength of monomer TiO2 in the ultraviolet region is 387.5nm, and the absorption wavelength of monomer Co3O4 in the visible light region is similar to that reported, due to the redistribution and transfer of interface charge from Co3O4 to TiO2. The absorption band can broaden the visible light region. Function (αhν)1 / n=A(hν-Eg) (where a is the absorption coefficient, h represents the Planck coefficient, v is the vibration frequency, E is the band gap, A is the proportionality constant, and n is the nature of the sample transition). In the optical transition process of semiconductor materials (Co3O4), electrons can directly transition from the valence band to the conduction band without the help of transition materials involving other particles such as phonons, so the relationship between the optical absorption coefficient and the photon energy can be described by the above function, so n is 1 / 2.

[0048] Example 6

[0049] The ternary composite material provided by the present invention can adsorb antibiotic solutions in water under visible light conditions. In particular, it can efficiently remove tetracycline antibiotics (TCs). The photocatalytic degradation of tetracycline solution (10 mg / L) was evaluated by simulating sunlight conditions with a xenon lamp. The absorbance of the tetracycline (TC) solution was detected at the maximum absorption wavelength of λ=357nm, and its degradation rate was calculated. The specific operation steps are as follows:

[0050] Weigh 10.5 mg of the binary composite material TiO2 / Co3O4, TiO2 / Co3O4 / AgBr ternary heterojunction composite material obtained in Examples 1-4, and monomer TiO2 and monomer Co3O4, respectively, add them to a photocatalytic reactor containing 40 mL tetracycline solution (10 mg / L), stir and disperse, and react in the dark for 30 minutes to allow the catalyst and tetracycline solution to reach adsorption equilibrium. After the dark reaction, draw 4 mL of the mixed solution respectively, filter the solid with a needle filter, and leave the clear liquid as a sample to be tested. Turn on a 250W xenon lamp for photocatalytic reaction, set the reaction time to 60 minutes, and during the reaction, use a sampling tube to draw about 4 mL of the mixed solution from the upper end of the reactor every 10 minutes. Finally, use an ultraviolet spectrophotometer (UV-Vis) to detect the absorbance of the upper clear liquid (357 nm, corresponding to the strongest absorption peak of tetracycline) and record the absorbance of the upper clear liquid, and calculate the treatment efficiency of the tetracycline solution respectively. The results are shown in Table 1.

[0051] Table 1. Degradation rate of tetracycline by the prepared composite materials

[0052]

[0053]

[0054] Figure 7 is the photodegradation diagram of tetracycline by the prepared composite material. Figure 7As shown in Table 1, compared with the monomer, the photocatalytic rate of the binary composite material TiO2 / Co3O4 provided by the present invention is improved, TiO2 and Co3O4 form a heterojunction to connect with each other, the separation of electron-hole pairs is accelerated, more active substances are promoted to participate in the reaction, and the ability of the catalyst to degrade tetracycline can be improved. When the molar ratio of TiO2 and Co3O4 is 9:1 (5-TCo), the degradation effect is improved best, and the degradation rate reaches 39.51%. Further modifying AgBr particles on the surface of the 5-TCo product to form a point-to-face contact heterojunction can further improve its electron transfer efficiency. The product 2-TCA modified with 20% AgBr particles has the best effect on tetracycline degradation under visible light conditions, and the degradation rate reaches 86.03% after 60 minutes of reaction. It shows that by modifying AgBr (with a narrower band gap) on the surface of the binary material, it can absorb light of a wider band and broaden the light response range of the entire composite material. The visible light absorption capacity of the composite ternary heterojunction photocatalytic material is stronger, and the separation of electrons and holes is accelerated.

[0055] Figure 8 is the EIS graph of TiO2, Co3O4, 5-TCo, and 2-TCA; in the figure, (a) is the photocurrent curve and (b) is the electrochemical impedance graph; Figure 8 It can be seen that the minimum arc of 2-TCA indicates that its charge transfer resistance is the lowest, which is conducive to efficient charge separation, which is consistent with the photocurrent response results. It is further confirmed that without setting an external voltage, 2-TCA can quickly and effectively separate and transfer charges during the photocatalytic process, reduce the recombination of electron-hole pairs, and improve the photocatalytic efficiency. This is consistent with the results of TC photocatalytic degradation, which together show that the excellent photocatalytic performance of 2-TCA is closely related to its efficient charge separation and transfer mechanism.

[0056] Fig. 9 It is the PL diagram of TiO2, Co3O4, 5-TCo, and 2-TCA. Fig. 9 It can be seen that the lowest emission peak intensity of 2-TCA indicates that its photogenerated electron-hole pairs are less, which is due to the construction of the heterostructure to improve the capture efficiency of electron-hole pairs and reduce the recombination of electron-hole pairs. The PL intensity of 5-TCo is lower than that of monomer TiO2, indicating that the heterostructure constructed with Co3O4 more effectively captures electron-hole pairs; after 5-TCo is modified with AgBr, the PL emission intensity of 2-TCA is enhanced, which can be attributed to the improved separation efficiency of ·OH radicals, indicating that the modification of AgBr helps to inhibit the photoinduced recombination of electron-hole pairs and improve the photocatalytic performance.

[0057] Fig.10 This is the MS diagram of TiO2, Co3O4, 5-TCo, and 2-TCA. Fig.10It can be seen that the potential point of 2-TCA at -0.55eV is unique to the TiO2 / Co3O4 / AgBr ternary heterojunction composite material. The appearance of this potential point is related to the new electronic structure and energy level state formed after AgBr is modified on the surface of TiO2 / Co3O4. The addition of AgBr not only changes the light absorption range of the material, but also affects the electron transfer process. At this potential, redox reactions related to AgBr may occur, or the synergistic effect between AgBr and TiO2 / Co3O4 may cause changes in the transmission and distribution of electrons in the composite material, thereby improving the photocatalytic activity of the material, making it exhibit excellent performance in processes such as photocatalytic degradation of tetracycline.

[0058] Fig.11 is the XPS graph of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material prepared in Example 3; Fig.11 It can be seen that the full spectrum scan shows the characteristic peaks of Ti, O, Co, Ag and Br. The peak at 458.8 eV in the Ti 2p spectrum corresponds to Ti 4+ The peak at 779.9eV in the Co 2p spectrum is the characteristic peak of Co. The changes in the binding energy of TiO2 and Co3O4 in the O1s spectrum indicate the formation of Co-O-Ti bonds, and the Ag3d and Br3d spectra also provide information on the chemical states of the corresponding elements. This proves that the prepared TiO2 / Co3O4 / AgBr ternary heterojunction composite material has ideal stability.

[0059] Fig.12 This is a graph showing the degradation effect of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material prepared in Example 3 after five cycles. Fig.12 It can be seen that with the increase in the number of cycles, the degradation efficiency of tetracycline gradually decreases, but even in the 5th cycle, the degradation efficiency can still be maintained at about 75%. This shows that the catalytic material has good photocatalytic stability and good repeatability, and still has considerable treatment effects after multiple catalytic degradations. It has great commercial promotion value in practical applications.

[0060] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a TiO2 / Co3O4 / AgBr ternary heterojunction composite material, characterized in that: The preparation method comprises the following steps: (1) TiO2 was added to anhydrous methanol and ultrasonically mixed until uniform, 2-methylimidazole was added and stirred to obtain a mixed solution A; a mixed solution of Co(NO3)36H2O and methanol was dropped into the mixed solution A, stirred at room temperature and precipitated and aged, the product was washed and dried, and calcined at high temperature to obtain a TiO2 / Co3O4 binary composite material; (2) The TiO2 / Co3O4 binary composite material prepared in step (1) is homogenized by ultrasonication in deionized water, Ag2SO4 is added and stirred evenly, and then potassium bromide aqueous solution is added under dark reaction conditions and stirred in the dark; the product is washed and centrifuged, and dried to obtain a TiO2 / Co3O4 / AgBr ternary heterojunction composite material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of Co(NO3)36H2O and TiO2 in the mixed solution A in step (1) is 3-27:

3.

3. The preparation method according to claim 1, characterized in that: The stirring time in step (1) is 1 h to 5 h, and the precipitation aging time is 3 h to 10 h.

4. The preparation method according to claim 1, characterized in that: The stirring time in step (1) is 3h-5h, and the precipitation aging time is 5h-10h.

5. The preparation method according to claim 1, characterized in that: In the TiO2 / Co3O4 / AgBr ternary heterojunction composite material in step (2), the mass fraction of AgBr in the TiO2 / Co3O4 / AgBr ternary heterojunction composite material is 10-40%.

6. The preparation method according to claim 1, characterized in that: In step (2), the dosage ratio of the TiO2 / Co3O4 binary composite material, deionized water, Ag2SO4, and potassium bromide aqueous solution is 0.0027 mol:100 mL:0.0013 mol:50 mL; the concentration of the potassium bromide aqueous solution is 0.016 mol / L.

7. The preparation method according to claim 1, characterized in that: The stirring time in step (2) is 2-8 hours, and the drying temperature is 50°C-80°C.

8. The TiO2 / Co3O4 / AgBr ternary heterojunction composite material prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the TiO2 / Co3O4 / AgBr ternary heterojunction composite material according to claim 8 in the field of antibiotic adsorption in water.

10. The use according to claim 9, characterized in that: The antibiotic is a tetracycline antibiotic.

Citation Information

Cited By

  • AgBr / Co / NiBr2 composite material catalyst as well as preparation method and application thereof

    CN120305990A

  • AgBr / Co / NiBr2 composite catalyst and its preparation method and application

    CN120305990B